(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2014)
In 2015, the Millennium Development Goals are due to end. Academics, practitioners and the general public are eager to see which development agenda will take their place and a variety of different organizations are currently elaborating proposals for the next “round” of goals and targets. Instead of investigating possible topics of the upcoming agenda, we focus on methodological questions that – according to our view – will play a major role in the definition and implementation of future development goals. We focus on the elaboration of some key questions that should be addressed in the realm of poverty and inequality measurement, the definition of targets, the ability to consider complexity and evidence-based policy making.